The Use of Information Gained under RTI Act- 2005 in Forensics and Toxicology- An Indian Perspective - Ankit Gupta; Vikas Gupta; Amar Pal Singh (Institute of Medico-legal Publications Pvt Ltd, 2021)
The role of forensic reports are to prove without doubt in the court the cause of death, injury nature of deathor accident but courts till date do not fully rely on forensic reports as evidence. A study conducted in 2011by Supreme Court and High Courts, DNA has played an important role in only 47 cases. Out of these, 23.4%decisions were given by Delhi High Court alone. Furthermore, DNA evidence had been used in merely4.7% murder cases and 2.3% rape and murder. The Committee on Reforms of Criminal Justice System alsosignifies that the present stage of applicability of forensic science in crime scene investigation is somewhatlow in our country, with only 5-6% of the registered crime cases being referred to the Forensic ScienceLaboratories (FSLs) and Finger Print Bureau put together.Article 20(3) of the Indian constitution states that “No person accused of any offence shall be compelled tobe a witness against himself but the honourable Supreme Court held otherwise. In the case of The State ofBombay vs Kathi Kalu Oghad And Others (AIR 1961), the Supreme Court held that, compelling any personto give any sort of forensic evidence does not violate Article 20(3) of the constitution. The same is givenin Section 73 of the Indian Evidence act, which states that any person can be asked to give the fingerprintor DNA examination even to the accused. Similarly, Section 53 of the criminal procedure code states thata person accused of any crime can be asked to undergo a medical examination if the officers feel that theexamination can provide some evidence to the crime. Further Section 164A of the procedure allows themedical examiner to examine the victim of the rape case within twenty-four-hours of the crime.